Reassessing UNHCR’s Role in Rohingya Resettlement: A Jus Cogens Perspective on Non-Refoulement - Nasution, Muhammad Rafli Fahriza; Harahap, Rabiah Z (Universitas Islam Negeri Alauddin Makassar, 2026)
The Rohingya refugee crisis remains one of the most protracted humanitarian emergencies, raising persistent questions regarding the implementation of the principle of non-refoulement in international refugee law. While previous studies have widely examined refugee protection and regional responses, limited scholarship specifically addresses the normative tension between the binding character of non-refoulement and the voluntary nature of third-country resettlement mechanisms. This study analyzes the legal status of non-refoulement and evaluates the role of the United Nations High Commissioner for Refugees (UNHCR) in Rohingya resettlement to third countries. Using normative legal research with statutory, conceptual, and doctrinal approaches, the study finds that non-refoulement has developed beyond treaty law into a widely recognized norm of customary international law, although its jus cogens status remains debated in academic literature. UNHCR plays a central operational role through refugee status determination, vulnerability assessment, case referral, pre-departure preparation, and post-arrival monitoring. However, its effectiveness is constrained by limited quotas, state sovereignty concerns, and the absence of binding obligations on receiving states. This article contributes by proposing a clearer distinction between non-refoulement as a mandatory protection norm and resettlement as a burden-sharing mechanism dependent on state consent. Strengthening global responsibility-sharing frameworks is therefore essential for more effective Rohingya protection.